USULAN PERBAIKAN KUALITAS PRODUK RANTAI BOILER MENGGUNAKAN METODE SIX SIGMA DAN TRIZ - Al-Faritsy, Ari Zaqi; Furqon, Ahmad Nurul (Nusantara of Engineering (NOE), 2023)
The problem that occurs at CV Sri Rejeki is that there are products that do not meet standards or defective products. Types of defective products include uneven surfaces and product shapes that do not match the mould. Defects that occur are caused by an Uneven Surface, which is caused during the process of pouring liquid metal into the mold, the pouring temperature is too low and the product shape does not match the mold, which is caused by the liquid metal raw material used is too bad and the pouring time is too long. This research method uses six sigma with DMAIC stages (Define, Measure, Analyze, Improve, and Control) with the help of pareto charts, and the TRIZ method (Teoria Rechenia Izobretatelskih Zadatchi). The biggest defect presentation is the uneven surface with a percentage level of 54%. The overall average DPMO value is 126920.25 and the sigma value is 2.65. From the fmea calculation, the highest RPN result is found in the expertise of workers with a scale value of 112. The proposed improvement is by holding routine training for employees at least 3 times a month at a mutually agreed time, as well as updating SOPs and printing them to minimize the occurrence of defective products. Also before carrying out the process of smelting raw materials, a separation process is carried out between feasible and inappropriate raw materials